Hierarchical emotional episodic memory for social human robot collaboration. Issue 5 (June 2018) - Lee, Won-Hyong; Kim, Jong-Hwan
Abstract For social human robot collaboration, robots need to effectively remember human experiences and manage emotional experiences as well as repetitive experiences. To implement these functions, the hierarchical emotional episodic memory, using deep adaptive resonance theory network, is proposed in this paper. The proposed memory not only learns emotional experiences, but also has the ability to anticipate future emotional situations. Two parameter modulation processes, delayed consolidation and instant update, are provided. These make emotional experiences reinforce faster, remain for longer, and become more stable and sensitive to analogous experiences. Simulation analysis is conducted to verify the proposed memory, and an experiment is carried out in a kitchen environment to demonstrate social human robot collaboration.